KARAKTERISTIK PENDERITA PENYAKIT JANTUNG KORONER YANG DIRAWAT INAP DI RSUD TANJUNG PURA TAHUN 2011-2012 - Christna Uly Simanjuntak; Jemadi ,MKes; Rasmaliah ,MKes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Coronary Heart Disease (CHD) is one of the most important heart disease because CHD is the main cause of mortality in some countries include Indonesia. In 2008, WHO informed cardiovascular disease PMR is 30% and died of CHD is 7,3 millions people. In 2007, Riskesdas collected CHD data based on diagnosis by healthcare professsional is 12,5%. In Semarang in 2004 CHD proportion is 26,00%. To know the CHD patients characteristics which are treated in RSUD Tanjung Pura in 2011-2012, descriptive research has been done with case series design. Population is 109 people and sample is same with population (Total Sampling). Data has been analyzed with Chi-Square, Mann-whitney, and Kruskal wallis test. The results shown that the highest CHD proportion based on sociodemographic, for female and male gender in the age group >60 years 22%, Javanese 74,3%, moslem 94,5%, housewifes 49,5%, married 88,1%, out of Tanjung Pura 61,5%, chest pain 77,1%, hypertension 89%, blood sugar level 65,1%, high total cholesterol 72,5%, Jamkesmas 64,2%, home medical treatment way 50,5%, CFR 7,3%. There is significant different age proportions based on blood pressure (p=0,002), blood sugar level (p=0,015). There is no significant different age proportions based on total cholesterol (p=0,068), the average treatment time based on age (p=0,199), the average treatment time based on cost source (p=0,303). There is significant different average treatment time based on blood pressure (p=0,093). There is no significant difference average treatment time based on blood sugar level(p=0,608). total cholesterol (p=0,468). There is significant differerent average treatment time based on condition when out (p=0,029). RSUD Tanjung Pura is expected to give information about risk factor of CHD and recommend medical check up regularly. The hospital is recommended to refer the patients as soon as possible if can not be handled. For Hypertention, DM, and Cholesterol patients are recommended to consume drug regularly, and medical check up to control their blood pressure, blood sugar level, and total cholesterol. Keywords : Coronary Heart Disease (CHD), Characteristic